2014
DOI: 10.1097/ico.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype–Genotype Correlation in Patients With Schnyder Corneal Dystrophy

Abstract: N102S may also be a mutation hotspot in the Polish population, as in other previously reported populations. Corneal crystals formed a characteristic pattern on optical coherence tomography scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Twenty-four mutations that alter twenty amino acid residues in UBIAD1 protein have been identified in SCD families (8,9). Asparagine-102 (N102) and glycine-177 (G177) are the most frequently altered UBIAD1 residues in SCD.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four mutations that alter twenty amino acid residues in UBIAD1 protein have been identified in SCD families (8,9). Asparagine-102 (N102) and glycine-177 (G177) are the most frequently altered UBIAD1 residues in SCD.…”
Section: Resultsmentioning
confidence: 99%
“…However, the number of patients examined was relatively low compared with that of the previous studies [13]. Absence of crystals renders the diagnosis of SCD more challenging and previous studies have shown the ability of modern imaging techniques such as SD-OCT and IVCM to identify the corneal features of SCD by allowing an in-depth evaluation of corneal structures [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Previously published data on SD-OCT in SCD included hyperreflective corneal opacities located under the epithelium and in the anterior stroma and a diffuse optical shadow from the stromal side [15].…”
Section: Discussionmentioning
confidence: 99%
“…On slit lamp biomicroscopy, such deposition may manifest as stromal mid‐peripheral corneal haze, crystal deposition and arcus lipoides (Fig. ) . Patients under the age of 23 years usually only have a central corneal opacity, with or without sub‐epithelial and anterior stromal polychromatic crystals, and have normal corneal sensation.…”
Section: Lipidmentioning
confidence: 99%
“…In vivo confocal microscopy has shown decreased sub‐basal nerve density and increased stromal reflectivity. Cases with crystalline deposits exhibited numerous needle shaped and rectangular highly reflective opacities in the anterior stroma …”
Section: Lipidmentioning
confidence: 99%